Rational design of a new mutant of tobacco etch virus protease in order to increase the in vitro solubility - Hossein Mohammadian; Karim Mahnam; Hamid Mirmohammad Sadeghi; Mohamad Reza Ganjalikhany; Vajihe Akbari (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Tobacco etch virus (TEV) protease is a protease with high sequence specificity which is useful for the cleavage of fusion proteins. A major limitation of this enzyme is its relatively poor solubility. This study aimed to investigate the effects of some suggested mutations by online tools and molecular dynamics simulation to improve the solubility of TEV protease in vitro. Experimental approach: We designed a rational multi-stage process to determine the solubilizing mutations of TEV protease. At the first stage, all the possible mutations were predicted using online tools such as PoPMuSiC and Eris servers, in which five mutations include N23F, N23L, Q74L, Q74V, and Q74I were suggested for further studies. In the next step, the three dimensional structure of the wild type (WT) and the best mutations were subjected to molecular dynamic simulations to evaluate the dynamic behaviour of the obtained structures. The selected mutation was introduced into the structure using site-directed mutagenesis and expressed in Escherichia coli BL21DE3. After purification, solubility and activity of the purified mutant and WT-TEV proteases were assayed. Findings /Results: By considering the analysis of various factors such as structural and solubility properties, one mutant, N23F, was selected for in vitro studies which led to a 1.5 times increase in the solubility compared to the WT while its activity was decreased somewhat. Conclusion and implications: We propose N23F mutation, according to computational and experimental analyses for TEV proteases which resulted in a 150% increase in solubility compared to the WT.